Analisis Variasi Genetik Melon (Cucumis melo L.) Kultivar Gama Melon Basket Dengan Metode Random Amplified Polymorphic DNA - Nur Huda, Ikhsan; Setiadi Daryono, Budi (Jurusan Biologi UIN Alauddin Makassar, 2013)
Melon (Cucumis melo L.) cultivars Gama Melon Basket (GMB) is the result of plant breeding that has the potential to be a product of local melon seed in Indonesia. This cultivar phenotype characters was known, but its genetic variation is not further studied. This study aimed to analyze the genetic variation of melon cultivars GMB and compared with 13 commercial melons and four members of the family Cucurbitaceae such as; cucumber, cucumber queen, barteh, and cantaloupe (blewah). RAPD-PCR method with 11 random primer was used to evaluate genetic variation in melon. Level of genetic similarity was determined by the formula simple matching coefficient (SSM) and the dendogram constructed by clustering analysis unweighted pair-group using arithmeticaverages (UPGMA). Results of RAPD-PCR with 11 primer produced 165 loci and it contains 84.85 % polymorphic DNA and 15.15 % monomorphic DNA. Results of genetic variation analysis suggests that 15 commercial melons differ from groups of cucumber, cucumber queen, barteh and cantaloupe(blewah). Cultivars GMB has genetic marker that can be distinguished from other commercial melons. GMB cultivar have specific polymorphic DNA on the size of 285 bp generated by PMAR primer.Keywords: Cucumis melo L., Gama Melon Basket, genetic variation, RAPD